Quantum coherence in molecular photoionization. Issue 33 (10th August 2022) - Ruberti, Marco; Patchkovskii, Serguei; Averbukh, Vitali
Abstract : Onset, decay, and control of ultrafast quantum coherence in many-electron systems is in the focus of interest of attosecond physics. We discuss electronic and nuclear dynamics affecting it, and outline directions for future study. Abstract : The study of onset and decay, as well as control of ultrafast quantum coherence in many-electron systems is in the focus of interest of attosecond physics. Interpretation of attosecond experiments detecting the ultrafast quantum coherence requires application of advanced theoretical and computational tools combining many-electron theory, description of the electronic continuum, including in the strong laser field scenario, as well as nuclear dynamics theory. This perspective reviews the recent theoretical advances in understanding the attosecond dynamics of quantum coherence in photoionized molecular systems and outlines possible future directions of theoretical and experimental study of coherence and entanglement in the attosecond regime.